The Ascetic Qur'an and Its Kharijite Readers - Schmid, Nora K., (Middle East and Islamic Studies E-Books Online, Collection 2025, 2025)
Research on Islamic asceticism frequently highlights practices and ideas described in premodern Islamic literature on renunciation ( zuhd ). This study redirects our attention to the Qur'an's ascetic dimension and its reception in the poems and sermons of the Kharijites, an early Islamic group known for extreme piety. It sheds light on the Qur'an's engagement with late antique ascetic ideas, notably regarding scriptural reading and recitation. In their reception of the Qur'an, the Kharijites developed practices of reading and recitation characterized by the interiorization and enactment of scripture. This book offers a new view of the religious culture of the first and early second centuries of Islam through the lens of an understudied group and its attempts to put the Qur'an into practice.